Preparation method and application of In2O3 / SCN composite photocatalyst

By preparing In2O3/SCN composite photocatalysts, the problem of poor performance of existing In2O3 photocatalysts is solved, and a higher catalytic effect and a wider photoresponse range are achieved, especially in the degradation of organic dyes and antibiotics, which show excellent catalytic performance.

CN119588399APending Publication Date: 2025-03-11ZHEJIANG UNIV OF TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411826250.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing In2O3 photocatalysts have poor effects in degrading organic pollutants or photocatalyzing hydrogen production, and catalytic performance needs to be improved.

Method used

Using the preparation method of In2O3/SCN composite photocatalyst, SCN material is obtained by mixing thiourea and urea in a specific ratio and calcining it, and then mixing with InCl3·4H2O and urea in water, drying and calcining it to obtain the In2O3/SCN composite photocatalyst.

Benefits of technology

By doping S element, the energy band structure of g-C3N4 is changed, the photoresponse range and catalytic effect of the catalyst are enhanced, and the degradation performance of organic dyes and antibiotics is improved, and the degradation rate reaches more than 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588399A_ABST
    Figure CN119588399A_ABST
Patent Text Reader

Abstract

The invention discloses an In2O3 / SCN composite photocatalyst preparation method, which comprises: grinding thiourea and urea according to a mass ratio of 1: 45-55, mixing, gradually heating to a temperature of 500-520 DEG C, and calcining the mixture to obtain an SCN material; dispersing the SCN material, urea and InCl3. 4H2O in water, stirring and mixing, and then drying to obtain a dried material; the dried material is gradually heated to 420-450 DEG C for calcination, and the In2O3 / SCN composite photocatalyst is obtained. According to the invention, one-dimensional rod-like In2O3 is constructed on a two-dimensional sulfur-doped carbon nitride nanosheet (hereinafter replaced by SCN) by adopting a hydration method, charge transfer is enhanced, and the specific surface area of the catalyst is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of worsted wool yarn blending, and specifically relates to an In 2 O 3 Preparation method and application of / SCN composite photocatalyst. Background Art

[0002] With the development of the pharmaceutical industry and the widespread use of antibiotics, a large amount of antibiotic-containing wastewater has entered the environment due to improper treatment, posing a major threat to the ecological environment and human health. At present, various methods, including adsorption, membrane filtration, biodegradation and advanced oxidation treatment processes (AOPs), are widely used in the regeneration and treatment of TC-contaminated wastewater. Among them, photocatalytic technology using sunlight as energy and semiconductor catalysts as carriers is widely used in the field of organic matter removal due to its advantages such as energy saving and environmental protection.

[0003] In the Chinese patent application publication number CN109999779A, an In 2 O 3 Photocatalyst and preparation method and use thereof, in which urea and InCl 3 Dissolve in deionized water. Then place the solution in an oil bath and heat for a period of time under magnetic stirring. After heating, take out the solution, cool to room temperature, collect the white product by centrifugation, wash and dry. Then dry In(OH) 3 Placed in a tube furnace, treated at high temperature in air atmosphere, In 2 O 3 Sample. The sample was treated with plasma technology to obtain the final oxygen-rich In 2 O 3 Sample. But the 2 O 3 There is room for improvement in terms of degradation of organic pollutants or photocatalytic hydrogen production, and the results are not good. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide an 2 O 3 The preparation method and application of the / SCN composite photocatalyst solve the above-mentioned technical problems existing in the prior art.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A kind of 2 O 3 The preparation method of the SCN composite photocatalyst comprises the following steps: S1. Grind thiourea and urea in a mass ratio of 1:45-55 and mix them, then gradually heat them to 500-520° C. and calcine the mixture to obtain SCN material; S2, SCN material, urea and InCl 3 ·4H 2 O is dispersed in water and stirred and mixed, and then dried to obtain a dried material; S3, gradually heating the dried material to 420-450°C for calcination to obtain In 2 O 3 / SCN composite photocatalyst.

[0006] Furthermore, in S1, thiourea and urea are mixed in a mass ratio of 1:50.

[0007] Furthermore, the temperature of the heating in S1 and S3 is controlled at 2-3°C / min; and the temperature is kept warm for 2-3h after the temperature is heated to the specified temperature.

[0008] Furthermore, in S2, the drying temperature is 50-60°C until the water is completely evaporated.

[0009] Furthermore, in S2, the mass ratio of SCN material to urea is 16:216.

[0010] Furthermore, in S2, InCl 3 ·4H 2 The mass ratio of O to SCN is 18×10 -3 :16.

[0011] Furthermore, in S2, the mass ratio of water to SCN material is 250:1.

[0012] Furthermore, in S2, the water used is deionized water.

[0013] Furthermore, the In 2 O 3 / SCN composite photocatalyst is used in photocatalytic degradation of organic dyes and antibiotics.

[0014] Beneficial effects of the present invention: 1. In the present invention, a hydration method is used to construct a one-dimensional rod-shaped In2O3 on a two-dimensional sulfur-doped carbon nitride (hereinafter referred to as SCN) nanosheet. 2 O 3 The S element is doped on the surface, which changes the gC 3 N 4 The energy band structure of the catalyst gives it a stronger light response range, compared to the traditional In 2 O 3, can obtain higher catalytic effect.

[0015] 2. The present invention directly 2 O 3 In situ synthesis of composite catalysts can enhance charge transfer and increase the specific surface area of ​​the catalyst.

[0016] 3. The composite photocatalyst used in the present invention is used for photocatalytic degradation of 20 mg / L tetracycline hydrochloride; it exhibits excellent catalytic performance, with a degradation rate of more than 90% in 120 min. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 It is a synthetic route diagram of the preparation method of the present invention; Figure 2 It is the XRD diffraction spectrum of the materials prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention; Figure 3 It is the infrared spectra of Example 1, Example 2 and Comparative Example 1 of the present invention; Figure 4 is a scanning electron microscope image of various materials of the embodiments of the present invention; Figure 5 In the embodiment of the present invention 2 O 3 Transmission electron microscopy image of / SCN composite material; Figure 6 In the embodiment of the present invention 2 O 3 / Element distribution map of SCN composite materials; Figure 7 is an XPS spectrum image of an embodiment of the present invention; Figure 8 is a UV-visible absorption spectrum and a Mott-Schottky curve diagram of an embodiment of the present invention; Fig. 9 It is a transient photocurrent response diagram and an electrochemical impedance spectroscopy Nyquist diagram of an embodiment of the present invention; Fig.10 is a series of diagrams of Example 3 of the present invention and photocatalytic degradation of tetracycline hydrochloride; Fig.11 It is a series of group pictures of Example 4 of the present invention and the photocatalytic degradation of nitrofurantoin. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] like Figure 1 As shown, this is an embodiment of the present application. 2 O 3 The preparation method of the SCN composite photocatalyst comprises the following steps: S1. Grind thiourea and urea in a mass ratio of 1:45-55 and mix them (preferably the mixing ratio is 1:50), then gradually heat up to 500-520°C, calcine the mixture, control the heating temperature at 2-3°C / min, and keep warm for 2-3h to obtain SCN material.

[0021] S2, SCN material, urea and InCl 3 ·4H 2 O is dispersed in deionized water and stirred and mixed, and then dried to obtain a dried material, and the drying temperature is 50-60°C until the water is completely evaporated; At this time, the mass ratio of SCN material and urea is 16:216; and InCl 3 ·4H 2 The mass ratio of O to SCN is 18×10 -3 :16; the mass ratio of water to SCN material used is 250:1.

[0022] S3, gradually heating the dried material to 420-450°C for calcination, controlling the heating temperature at 2-3°C / min, and keeping the temperature for 2-3h to obtain In 2 O 3 / SCN composite photocatalyst.

[0023] In 2 O 3 / SCN composite photocatalyst is used in photocatalytic degradation of organic dyes and antibiotics.

[0024] In the present application, the S-doped g-C3N4 has stronger photocatalytic activity, more favorable redox performance and visible light absorption efficiency, and also broadens the response to the light range. Since the ionic radius and electronegativity of element S are comparable to those of element N, S may replace g-C3N4 in the doping process. 3 N 4 The defect structure formed by N in gC3 N 4 The interlayer order of gC increases the reaction sites, thereby enhancing the photocatalytic activity. At the same time, a series of semiconductor photocatalysts with matching energy band structures are selected to 3 N 4 Constructing heterojunction. Indium oxide (In 2 O 3 ) has the characteristics of high dielectric constant and low resistivity, and is selected with S-doped gC 3 N 4 By constructing a heterojunction, its special electron transfer mode can effectively inhibit the recombination of electron-hole pairs and extend the lifetime of photogenerated carriers.

[0025] Therefore, it is combined with S-doped gC 3 N 4 The coupling can obtain the following results: 1. The interface structure is conducive to the diffusion and transfer of carriers; 2. The synergistic effect of the two after the heterojunction is formed.

[0026] Embodiment 1: Step 1: Put 5 g of urea and 0.1 g of thiourea into a mortar and grind them thoroughly to obtain a grind; Step 2: The ground product obtained in the first step is placed in a porcelain boat and heated in a tube furnace at 520°C, with a gradual heating rate of 2°C / min and a holding time of 2h; Step 3: The sample obtained in step 2 is ground to obtain SCN nanosheets.

[0027] Embodiment 2: In the first step, 18 mg InCl 3 ·4H 2 O drug is dispersed in 40mL deionized water to obtain a mixed solution A; Step 2: quantitatively add 0.16 g SCN and 2.16 g urea to the mixed solution A obtained in the first step, and stir for 2 h to obtain a mixed solution B; Step 3: The mixed solution B obtained in step 2 is transferred to a 60°C oven until the solution is dried; Step 4: The sample obtained in step 3 was ground into a mortar, placed into a porcelain boat and heated at 450°C in a tube furnace at a heating rate of 2°C / min for 2 hours. Embodiment 3: The first step is to add 20mgIn 2 O 3 The / SCN composite material was dispersed in 50 mL of 20 mg / L tetracycline hydrochloride solution and stirred in a dark room for 1 h; In the second step, the suspension obtained in the first step was placed under a 300W xenon lamp (λ>420nm) for illumination, and 3mL of liquid was taken at 20-minute intervals; In the third step, the liquid sample obtained in the second step was centrifuged at 9000 r / min for 1 min to remove the catalyst; In the fourth step, the liquid obtained after centrifugation in the third step is tested in a UV-visible spectrophotometer to evaluate the photocatalytic performance.

[0028] Embodiment 4: The first step is to add 20mgIn 2 O 3 / SCN composites were dispersed in 50 mL of 10 mg / L nitrofurantoin solution and stirred in a dark room for 1 h; In the second step, the suspension obtained in the first step was placed under a 300W xenon lamp (λ>420nm) for illumination, and 3mL of liquid was taken at 20-minute intervals; In the third step, the liquid sample obtained in the second step was centrifuged at 9000 r / min for 1 min to remove the catalyst; In the fourth step, the liquid obtained after centrifugation in the third step is tested in a UV-visible spectrophotometer to evaluate the photocatalytic performance.

[0029] Comparative Example 1: The first step is to add 2gInCl 3 ·4H 2 O was placed in a porcelain boat and heated at 450°C in a tube furnace at a heating rate of 2°C / min and a holding time of 2h; In the second step, the product of the first step is ground to obtain In 2 O 3 Nanorods.

[0030] Comparative Example 2: In the first step, 9 mg InCl 3 ·4H 2 OThe drug is dispersed in 40mL of deionized water; In the second step, 0.16 g SCN and 2.16 g urea were quantitatively added to the solution obtained in the first step and stirred for 2 h; In the third step, the solution obtained in the second step is transferred to a 60°C oven until the solution is dried; Step 4: Grind the sample obtained in step 3 thoroughly in a mortar, put it in a porcelain boat and heat it in a tube furnace at 450°C at a heating rate of 2°C / min and a holding time of 2h.

[0031] Comparative Example 3: In the first step, 36 mg InCl 3 ·4H 2 OThe drug is dispersed in 40mL of deionized water; In the second step, 0.16 g SCN and 2.16 g urea were quantitatively added to the solution obtained in the first step and stirred for 2 h; In the third step, the solution obtained in the second step is transferred to a 60°C oven until the solution is dried; Step 4: Grind the sample obtained in step 3 thoroughly in a mortar, put it in a porcelain boat and heat it in a tube furnace at 450°C at a heating rate of 2°C / min and a holding time of 2h.

[0032] Comparative Example 4: In the first step, 72 mg InCl 3 ·4H 2 OThe drug is dispersed in 40mL of deionized water; In the second step, 0.16 g SCN and 2.16 g urea were quantitatively added to the solution obtained in the first step and stirred for 2 h; In the third step, the solution obtained in the second step is transferred to a 60°C oven until the solution is dried; Step 4: Grind the sample obtained in step 3 thoroughly in a mortar, put it in a porcelain boat and heat it in a tube furnace at 450°C at a heating rate of 2°C / min and a holding time of 2h.

[0033] like Figure 2 As shown, the XRD diffraction spectra of the materials prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 are shown. 2 O 3 The six characteristic diffraction peaks correspond to In 2 O 3 The (211), (222), (400), (422), (422), (422), (440) and (622) planes are located at 2 = 21.2°, 30.6°, 35.5°, 45.7°, 45.7°, 50.1° and 60.7°, respectively. Comparative Examples 2, 3 and 4 all have gC 3 N 4 andIn 2 O 3 The crystal structure of In 2 O 3 The increase in content belongs to In 2 O 3 The diffraction characteristic peak of In 2 O 3 With the increase of In content, the width of the characteristic diffraction peak of the composite material at 27.58° becomes wider. This is due to 2 O 3 The intervention changed the lattice constant of SCN.

[0034] Figure 3 Infrared spectra of the materials prepared in Example 1, Example 2 and Comparative Example 1. At 3189 cm −1The rather broad absorption peaks near 1634, 1575, 1417, 1325 and 1250 cm-1 are attributed to the stretching vibration bands of the remaining N−H units. −1 The peak at 809 cm-1 is attributed to the stretching mode of the C−N heterocycle, while the peak at 809 cm-1 is attributed to the stretching mode of the C−N heterocycle. −1 The sharp peaks nearby belong to the out-of-plane breathing vibration of the aromatic CN heterocycle. 3 N 4 formation.

[0035] Figure 4 (a) is a scanning electron microscope image of the SCN nanosheet material prepared in Example 1, and (b) is a scanning electron microscope image of the In nanosheet material prepared in Comparative Example 1. 2 O 3 Scanning electron microscopy image of nanorod material, (c) is In prepared in Example 2 2 O 3 Scanning electron micrograph of / SCN composite material.

[0036] like Figure 5 As shown, (d) and (e) are In prepared in Example 2 2 O 3 Transmission electron microscope image of the / SCN composite material. Rod-shaped In 2 O 3 Supported on a sheet of SCN, the lattice spacing of 0.292 nm corresponds to In 2 O 3 The (222) plane.

[0037] like Figure 6 As shown, (f) is In prepared in Example 2 2 O 3 The element distribution diagram of the / SCN composite material shows that In 2 Successful synthesis of O / SCN composites.

[0038] Figure 7 The XPS spectra of C1s, N1s, O1s and In3d of Example 1, Example 2 and Comparative Example 1 are shown in Table 1. The test results prove the successful synthesis of the composite material and its internal interaction. The in-situ calcination synthesis method enhances the SCN and In 2 O 3 The interfacial interaction between the two significantly changes the formed In 2 O 3 The element electron cloud density in the SCN composite further improves the carrier mobility in the composite and enhances the In 2 O 3 The above changes in XPS indicate that the activity of SCN and In 2 O3 A heterojunction is formed.

[0039] Figure 8 (a) is the UV-visible absorption spectra of Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4. 2 O 3 Afterwards, the absorption edge of the composite samples showed a red-shift trend, which means that they have a narrower bandgap structure and higher light absorption.

[0040] (c) and (d) are SCN and In respectively. 2 O 3 The Mott-Schottky curve is given by the formula: CB =E CB(Ag / AgCl) +0.197V (NHE) is converted to CB potential. By the following formula: αhv = A (hv-Eg) n Calculate (b) the Tauc curve and obtain SCN and In 2 O 3 The band gaps of E and E are calculated to be 2.59 eV and 2.46 eV respectively. VB =E g +E CB Calculate SCN and In 2 O 3 VB potential.

[0041] Fig. 9 (a) Example 1, Example 2 and Comparative Example 1 were subjected to transient photocurrent response analysis. 2 O 3 In comparison, IC2 shows a higher transient photocurrent density, indicating that the formation of the heterojunction enables IC2 to have more photogenerated carriers after photoexcitation.

[0042] and Fig.11 (b) SCN, In 2 O 3 The Nyquist plot of the electrochemical impedance spectroscopy of IC2 shows that In 2 O 3 >SCN>IC2. This further illustrates the inference that the composite material exhibits reduced resistance and enhanced electron transfer efficiency relative to the single material.

[0043] Fig.10 and Fig.11(a) and (b) are the degradation curve images and kinetic equation images of Example 3 and Example 4, respectively. From the degradation results, the performance of IC2 composite catalyst is greater than that of a single catalyst. Within 120 minutes, the degradation effect of 20 mg / L tetracycline hydrochloride is greater than 90%, and the degradation effect of 10 mg / L nitrofurantoin is greater than 72%. At the same time, in order to study Na + , K + Mg 2+ , Cl - 、NO 3 - 、SO 4 2- The effect of IC2 composite photocatalyst on the degradation of tetracycline hydrochloride was studied by using IC2 composite photocatalyst as raw material. In the second step of Example 3 and Example 4, 5 mg NaCl, KCl, and MgCl were added respectively. 2 、NaNO 3 and Na 2 SO 4 The sampling interval of the catalytic process was changed to every 10 minutes. Fig.10 (c), (d) and Fig.11 (c) and (d) are shown. + , K + Mg 2+ After that, the degradation performance of IC2 decreased. Similarly, adding Cl - 、NO 3 - 、SO 4 2- After that, the adsorption capacity of IC2 also decreased. The above shows that in the reaction system, competitive reactions occur with anions or cations to adsorb pollutants on the catalyst surface, occupying some active sites and thus weakening the catalytic activity.

[0044] In order to test the stability of the catalyst, a cyclic degradation experiment was carried out on the catalyst. The specific operation was as follows: the catalyst was collected in step 3 of Examples 3 and 4, dried, ground and added to the next degradation experiment. The sampling interval of the catalytic process was also changed to once every 10 minutes. Fig.10 (d) and Fig.11 (d) is the result of five cycles. After 60 minutes of degradation of tetracycline hydrochloride, the degradation efficiency decreased from 76% to 61%. After five cycles of degradation of nitrofurantoin for 60 minutes, the degradation efficiency decreased from 61% to 45%. The photocatalytic mechanism of the catalyst was explored by free radical capture experiments.

[0045] The experimental steps are as follows: In the second step of Example 3 and Example 4, 5 mg of ammonium formate and isopropanol were added and nitrogen was passed for half an hour before the photocatalytic degradation step was carried out. The sampling interval was also 10 minutes. Fig.10 (f) and Fig.11 (f) When isopropanol was added, the degradation effect was the worst, indicating that the masking of -OH had the greatest impact on the photocatalytic effect, indicating that -OH plays an important role in the IC2 sample system. After adding ammonium formate and nitrogen, the degradation effect was also weakened, indicating that H + and -O 2 - It also has a certain influence on photocatalytic degradation. In summary, the combined effect of these three free radicals in the IC2 sample system improves the photocatalytic efficiency. From the free radical capture experiment, we can know that -OH is the main factor leading to degradation, H + and -O 2 - is a minor contributor.

[0046] In summary, In with excellent photocatalytic performance can be obtained by simple calcination. 2 O 3 / SCN composites, which will provide a potential new photocatalyst and a new method for preparing composite photocatalysts for the purification of environmental pollutants.

[0047] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing an In2O3 / SCN composite photocatalyst, characterized in that: The following steps are involved: S1. Grind thiourea and urea in a mass ratio of 1:45-55 and mix them, then gradually heat them to 500-520° C. and calcine the mixture to obtain SCN material; S2, dispersing the SCN material, urea and InCl3·4H2O in water and stirring and mixing, and then drying to obtain a dried material; S3. Gradually heat the dried material to 420-450° C. for calcination to obtain an In2O3 / SCN composite photocatalyst.

2. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 1, characterized in that: In S1, thiourea and urea are mixed in a mass ratio of 1:

50.

3. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 1, characterized in that: The temperature of the heating in S1 and S3 is controlled at 2-3°C / min; after the temperature is heated to the specified temperature, the insulation time is 2-3h.

4. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 1, characterized in that: In S2, the drying temperature is 50-60°C until the water is completely evaporated.

5. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 1, characterized in that: In the S2, the mass ratio of SCN material to urea is 16:

216.

6. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 5, characterized in that: In the S2, the mass ratio of the amount of InCl3·4H2O to the amount of SCN material is 18×10 -3 :

16.

7. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 5, characterized in that: In S2, the mass ratio of water to SCN material is 250:

1.

8. The method for preparing the In2O3 / SCN composite photocatalyst according to claim 5, characterized in that: In S2, the water used is deionized water.

9. The method for preparing the In2O3 / SCN composite photocatalyst according to any one of claims 1 to 8, characterized in that: The In2O3 / SCN composite photocatalyst is used in photocatalytic degradation of organic dyes and antibiotics.

Citation Information

Patent Citations

  • In2O3 photocatalyst as well as preparation method and application thereof

    CN109999779A